Re-repair vs. Replacement for Failed Mitral Valve Repair: A Systemic Review and Meta-Analysis - Zhong, Zhaoji; Xu, Hang; Song, Wu; Liu, Sheng (Frontiers in Cardiovascular Medicine, 2022)
Objectives. To compare outcomes of re-repair versus mitral valve replacement (MVR) for failed initial mitral valve repair (MVr). Methods. We searched Pubmed, Embase, and Cochrane Library databases databases for studies that compared mitral valve re-repair and MVR for the treatment of failed initial MVr. Data were extracted by 2 independent investigators and subjected to a meta-analysis. Odd ratio (OR), risk ratio (RR), hazard ratio (HR), ratio difference (RD); mean difference (MD), and the 95% confdence interval (CI) were calculated by the Mantel-Haenszel and inverse-variance methods, for mode of repair failure, peri-operative outcomes, and follow-up outcomes. Results. Eight retrospective cohort studies were included, with a total of 938 patients, and mean/median follow-up ranged from 1.8 to 8.9 years. Pooled incidence of technical failure was 41% (RD: 0.41; 95% CI: 0.32 to 0.50; P = 0.00; I2 = 86%; 6 studies, 846 patients). The pooled mitral valve re-repair rate was 36% (RD: 0.36; 95% CI: 0.26 to 0.46; P = 0.00; I2 = 91%; 8 studies, 938 patients). Pooled data showed significantly lower peri-operative mortality (RR: 0.22; 95% CI: 0.07 to 0.66; I2 =0%; P=0.008; 6 studies, 824 patients), and significant lower long-term mortality (HR: 0.42; 95% CI: 0.30 to 0.58; I2 = 0%; P=0.00; 7 studies, 903 patients) in the re-repair group compared with MVR. Conclusions. Mitral valve re-repair was associated with better immediate and sustained outcomes for failed MVr, and should be recommended if technically feasible.